The effect of LiF, CaF2 and MgF2 Addition on the Sintering and Crystallisation Behaviour of a Base Glass Containing Calcined Bone Ash - Basaran, Neslihan; Capoglu, Ahmet (Elsevier, 2021)
The effect of adding individually LiF, CaF2, and MgF2 on the densification and crystallisation behaviours of a glass, which was designed by using considerable amount of calcined bovine bone ash in the batch formulation to develop crystalline phases that would provide both bioactivity and machinability when it is converted to a glassceramic, was studied. Sinter-crystallisation method was adopted for the conversion of a glass to a glass-ceramic. It was found that it would be possible to densify up to 87% relative density and crystallise the glasses after sintering at 700 ?C for 2 h. Kinetics study revealed that the activation energy values of glasses for crystallisation were 298, 306, and 344 kJoule/mole for glasses added with LiF (Glass 7), CaF2 (Glass 8) and MgF2 (Glass 9), respectively, by applying the Kissinger method. Major crystalline phases namely, fluorapatite, hydroxyapatite, and nepheline, dominated microstructure of all the glass ceramics produced from parent glasses.
Keywords: Calcined bone ash; Fluorapatite; Glass-ceramic; Hydroxyapatite; Nepheline